Bacillus Calmette-Guerin alleviates airway inflammation and remodeling by preventing TGF-β1 induced epithelial–mesenchymal transition. Issue 8 (3rd August 2017) - Tian, Xinrui; Tian, Xinli; Huo, Rujie; Chang, Qin; Zheng, Guoping; Du, Yan; Chen, Yan; Niu, Bo
ABSTRACT: Bacillus Calmette-Guerin (BCG) is a potent agent for the prevention of tuberculosis. Current studies have regarded BCG as an immunomodulator. However, there is little information on whether it can be used to inhibit airway inflammation and airway remodeling caused by asthma. Therefore, in this study, we investigate the role of epithelial–mesenchymal transition (EMT) in airway inflammation and airway remodeling as well as the possible therapeutic mechanism of BCG for the treatment of asthma. Wistar rats were sensitized and challenged by ovalbumin for 2 weeks or 8 weeks. BCG was subcutaneously administered daily before every ovalbumin challenge to determine its therapeutic effects. The 2 weeks model group showed extensive eosinophilia, chronic inflammatory responses, bronchial wall thickening, airway epithelium damage, increased levels of transforming growth factor β 1 (TGF-β1 ) in both bronchoalveolar lavage fluid and sera, decreased expression of epithelial marker E-cadherin, and increased expressions of mesenchymal markers α-smooth muscle actin (α-SMA) and Fibronectin (Fn). Except for inflammatory responses, all responses were more significant in the 8 weeks model group which displayed characteristics of airway remodeling including subepithelial fibrosis, smooth muscle hypertrophy, and goblet cell hyperplasia. When compared with the model groups, BCG administration inhibited airway inflammation and airway remodeling, decreased TGF-β1 levels, upregulated expression of E-cadherin, and downregulated expression of α-SMA and Fn. The present study suggests for the first time that increased secretion of TGF- β1 induced by asthmatic chronic inflammation may result in EMT, which is one of the most important mechanisms of airway inflammation and airway remodeling seen with asthma. BCG alleviates airway inflammation and airway remodeling by preventing TGF-β1 induced EMT, therefore BCG may be a new therapy for treating asthma.